The Border Between History and Literature. a Lecture of Luis Durand and the Agrarian Reform en Chile - Acevedo-Arriaza, N (UNIV SANTIAGO CHILE, INST ESTUDIOS AVANZADOS, 2019)
The following article discusses the vision of agrarian society at the beginning of the 20th century, based on the relationship between literature and historiography. From a critical analysis of the literature of Luis Durand it can be seen that he anticipates problems that the historiography on the Araucania studied later. In this sense, Durand s literature was a pioneer in the construction of representations of the subjects involved in the border society, but with an integrationist intentionality to the Chilean state and marked by a naturalization of social inequalities based on gender, race and class factors.